The Influenced Factors of the Switching Customer to Halal Cosmetic Products - Yasin, Rozaq M.; Norjanah, Siti (Indonesian Journal of Halal Research, 2021)
Ideally, a Muslim will easily decide to consume cosmetic product that have a halal label compared to cosmetic product that are not yet labeled halal. However, there are many people who switch use of product even though they are labeled halal. This study aims to analyze behavior patterns and factors that probability influence customers to switch away from halal cosmetic products. This study used primarly data with purposive sampling of 100 respondents in special region of Yogyakarta. Using logistic regression, the results show that the behavior pattern of customer switching for halal cosmetic products was dominated by the Millennial generation who have high curiosity and aggressiveness so that this generation’s behavior tends to be disloyal, including consuming cosmetics with halal products. Pricing, sales promotion, reputation and sales ethics have probability to influence customer switching behavior of halal cosmetic products. The halal cosmetic industry needs to pay attention to the behavior patterns of millennial generation, especially in terms of factors that probability influence to switch from halal cosmetic products.